Rancang Bangun Sistem Kehadiran Berbasis Mapping Location - Alhamidi; Rini Asmara; Eka Iswandy; Arif Budiman (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2022)
Utilization of technology is an essensial needs of the Gunung Mas Cell Padang Counter for managing employee attendance data which is has many branches in the West Sumatra area. At this time the management of employee attendance data uses the Whatsapp application. This presence consist of the employee's entry and completion hours. The method of taking presence on WhatsApp is by using direct photo taking and using the share location feature to find out whether the employee is really at the location of the counter in concerned. The use of the WhatsApp application makes counter management overwhelmed and has difficulty checking the attendance of its employees because the data sent on WhatsApp is not properly organized. For that we need an information system that can solve this problem. With this Mapping Location-Based Attendance System Application, it is hoped that it can provide accurate and detailed reports on employee attendance and existence so that it will be easier for employees to provide proof of attendance and assist the management of the Gunung Mas Cell Padang Counter in managing employee attendance data so that it can run well and effective.